a-minimal sets and related topics in transformation semigroups (I) - Masoud Sabbaghan; Fatemah Ayatollah Zadeh Shirazi (International Journal of Mathematics and Mathematical Sciences)
We deal with a-minimal sets instead of minimal right ideals of the enveloping semigroup and obtain a partition of disjoint isomorphic subgroups of some of its subsets. We also give some generalizations of almost periodicity and distality in the transformation semigroups and obtain similar results.